2020
DOI: 10.3390/ijms21030822
|View full text |Cite
|
Sign up to set email alerts
|

miR-21-KO Alleviates Alveolar Structural Remodeling and Inflammatory Signaling in Acute Lung Injury

Abstract: Acute lung injury (ALI) is characterized by enhanced permeability of the air–blood barrier, pulmonary edema, and hypoxemia. MicroRNA-21 (miR-21) was shown to be involved in pulmonary remodeling and the pathology of ALI, and we hypothesized that miR-21 knock-out (KO) reduces injury and remodeling in ALI. ALI was induced in miR-21 KO and C57BL/6N (wildtype, WT) mice by an intranasal administration of 75 µg lipopolysaccharide (LPS) in saline (n = 10 per group). The control mice received saline alone (n = 7 per gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Mice were anesthetized with Isoflurane in a plastic box with controlled ventilation and put in a supine position of head‐up on the board tilted at 30°. LPS at 1000 μg/mL was intratracheally administered to mice at a volume of 1 mL/kg mice body weight (BW) 16 . Animals for controls received the same manipulations and volume of PBS at 1 mL/kg BW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were anesthetized with Isoflurane in a plastic box with controlled ventilation and put in a supine position of head‐up on the board tilted at 30°. LPS at 1000 μg/mL was intratracheally administered to mice at a volume of 1 mL/kg mice body weight (BW) 16 . Animals for controls received the same manipulations and volume of PBS at 1 mL/kg BW.…”
Section: Methodsmentioning
confidence: 99%
“…LPS at 1000 μg/mL was intratracheally administered to mice at a volume of 1 mL/kg mice body weight (BW). 16 Animals for controls received the same manipulations and volume of PBS at 1 mL/kg BW. Mice remained in the position until regaining of consciousness and then had access to food and water ad libitum.…”
Section: Induction Of Acute Lung Injurymentioning
confidence: 99%
“…18 Consistent with our results, Jansing et al demonstrated that miR-21 knock-out alleviated alveolar structural remodelling and inflammatory signalling in ALI. 10 Therefore, miR-21 may exert its roles depending on different cell types and species.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In addition, miRNAs have been identified to be upregulated in inflammatory conditions, such as miR-155 9 and miR-21. 10 Jansing et al demonstrated that inflammatory reactions were impaired in miR-21 knock-out mice with reduced platelet and neutrophil activation compared to wild type (WT) mice that showed inflammatory and pathological changes in the presence of LPS. 10 However, more in vitro assays and in vivo experiments should be explored to elucidate the mechanisms underlying miR-21-involved ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Another evidence in favour of the association between miRNAs and inflammatory cytokines was seen for miR-21, an oncogene, profibrotic molecule that, at least in murine models, was seen to be associated with acute inflammatory processes at the lung level mediated by the classic “triad” of pro-inflammatory cytokines, IL-1β, IL-6, TNF-α [ 8 , 9 ]. Besides, it was also seen that its upregulation increases the expression of IL-8 and tumorigenesis in airway epithelial cells exposed to cigarette smoke [ 10 ].…”
Section: Role For Mirna In Respiratory Syndromesmentioning
confidence: 99%